Kajian Komparatif antara Pinjaman Berbasis Bunga dan Jual Beli Berbasis Mark-Up - Sanurdi, Sanurdi (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
Reward and punishment are also discussed in Islamic law. If people don’t obey the God’s rules, they will not get what they want. On the other hand, human right is such as a formula which contains some freedom such as freedom of speech, express, to have religion, and freedom of fear of war. Islam itself already contains such human right.